PENERAPAN MODEL INTEGRASI BIBLIKA BRYAN SMITH TAHAP 2 PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN WAWASAN KRISTEN ALKITABIAH (WAK) SISWA KELAS XI IPA-2 DI SUATU SMA DI TORAJA [THE IMPLEMENTATION OF THE BRYAN SMITH STAGE 2 BIBLICAL INTEGRATION MODEL IN LEARNING MATHEMATICS TO IMPROVE THE UNDERSTANDING OF A BIBLICAL CHRISTIAN WORLDVIEW (BCW) OF GRADE 11 SCIENCE-2 STUDENTS IN A HIGH SCHOOL IN TORAJA] - Adhi, Yoel; Winardi, Yonathan; Listiani, Tanti (Universitas Pelita Harapan, 2018)
This article discusses the problem of students’ poor understanding of a Biblical Christian Worldview (BCW) as related to their learning mathematics. The problem was discovered through tests and observations that the researcher conducted in a class of grade 11 Science-2 students at a high school in Toraja. The pre-cycle result showed that 23 students had a poor BCW understanding of mathematics. To improve students’ BCW understanding of mathematics, the researcher implemented the Bryan Smith Stage 2 Biblical Integration Model. The instruments that were used were teacher-mentor and peer-teacher observation sheets, student questionnaires, and simple understanding tests. Results showed improvements on the indicator of Creation from 96,2% in the first cycle to 100% in the second cycle, the indicator of Fall 100% in the first and the second cycles, and the indicator of Redemption from 88.8% in the first cycle to 92.5% in the second cycle. Over all, it could be concluded that the implementation of the Bryan Smith Stage 2 Biblical integration model could improve students’ BCW understanding in learning mathematics.BAHASA INDONESIA ABSTRACT: Artikel ini membahas permasalahan mengenai pemahaman Wawasan Kristen Alkitabiah (WAK) siswa yang rendah pada pembelajaran Matematika. Permasalahan tersebut ditemukan berdasarkan observasi dan tes yang dilakukan oleh peneliti di Kelas XI IPA-2 di suatu SMA di Toraja. Hasil prasiklus menunjukkan bahwa 23 siswa memiliki pemahaman BCW yang rendah pada pembelajaran Matematika. Untuk meningkatkan pemahaman BCW siswa pada pembelajaran Matematika, maka penelitian ini menerapkan integrasi Alkitab model Bryan Smith tahap 2. Instrumen yang digunakan adalah lembar observasi guru mentor dan teman sejawat, lembar angket siswa, serta lembar tes pemahaman sederhana. Dari hasil analisis dan pembahasan dapat dilihat peningkatkan pada indikator Creation dari 96,2 % di siklus I menjadi 100% di siklus II, indikator Fall 100% di siklus I dan siklus II, serta indikator Redemption dari 88,8% di siklus I menjadi 92,5% di siklus II. Secara keseluruhan penelitian menyimpulkan bahwa penerapan model integrasi Bryan Smith tahap 2 dapat meningkatkan pemahaman BCW siswa pada pembelajaran Matematika.